Hydrogenation properties of lithium and sodium hydride – closo-borate, [B10H10]2− and [B12H12]2−, composites. Issue 23 (4th June 2018) - Jensen, Steffen R. H.; Paskevicius, Mark; Hansen, Bjarne R. S.; Jakobsen, Anders S.; Møller, Kasper T.; White, James L.; Allendorf, Mark D.; Stavila, Vitalie; Skibsted, Jørgen; Jensen, Torben R.
Abstract : The hydrogen absorption properties of metal closo -borate/metal hydride composites are studied under high hydrogen pressures. Abstract : The hydrogen absorption properties of metal closo -borate/metal hydride composites, M2 B10 H10 –8MH and M2 B12 H12 –10MH, M = Li or Na, are studied under high hydrogen pressures to understand the formation mechanism of metal borohydrides. The hydrogen storage properties of the composites have been investigated by in situ synchrotron radiation powder X-ray diffraction at p (H2 ) = 400 bar and by ex situ hydrogen absorption measurements at p (H2 ) = 526 to 998 bar. The in situ experiments reveal the formation of crystalline intermediates before metal borohydrides (MBH4 ) are formed. On the contrary, the M2 B12 H12 –10MH (M = Li and Na) systems show no formation of the metal borohydride at T = 400 °C and p (H2 ) = 537 to 970 bar. 11 B MAS NMR of the M2 B10 H10 –8MH composites reveal that the molar ratio of LiBH4 or NaBH4 and the remaining B species is 1 : 0.63 and 1 : 0.21, respectively. Solution and solid-state 11 B NMR spectra reveal new intermediates with a B : H ratio close to 1 : 1. Our results indicate that the M2 B10 H10 (M = Li, Na) salts display a higher reactivity towards hydrogen in the presence of metal hydrides compared to the corresponding [B12 H12 ] 2− composites, which represents an important step towards understanding the factors that determine the stability and reversibility of high hydrogen capacity metal borohydrides for hydrogen storage.